2021
DOI: 10.1515/opar-2020-0172
|View full text |Cite
|
Sign up to set email alerts
|

Waterscape and Floods Management of Greek Selinus: The Cottone River Valley

Abstract: This paper investigates water bodies in the Greek colony of Selinus, Western Sicily-Italy. It focuses especially on one of the two rivers of the city: the Cottone. The investigative strategy adopted in this study consists of an interdisciplinary approach based on the analysis of archaeological evidence, Earth Sciences data, and the study of historical cartography. Results indicate that the Cottone River was not a swampy and unhealthy intermittent stream as it was believed so far; it was instead a fully functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There is also little information about the topographic features of the valleys and the location and extent of the ancient courses of the two rivers flowing along the flanks of the colony. Some information about the palaeogeography of the area comes from historical documents, maps, or travel reports, e.g., [9], and is supplemented by the results of archaeological excavations and geological and geophysical surveys. Two stratigraphic drillings reaching a depth of 15 m in the valleys of the Modione and Cottone rivers have shown that they are very different from each other [11], with the western valley characterized by a quite uniform fluvial sedimentation and the eastern one showing the characteristics of a former lagoon connected to the sea.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is also little information about the topographic features of the valleys and the location and extent of the ancient courses of the two rivers flowing along the flanks of the colony. Some information about the palaeogeography of the area comes from historical documents, maps, or travel reports, e.g., [9], and is supplemented by the results of archaeological excavations and geological and geophysical surveys. Two stratigraphic drillings reaching a depth of 15 m in the valleys of the Modione and Cottone rivers have shown that they are very different from each other [11], with the western valley characterized by a quite uniform fluvial sedimentation and the eastern one showing the characteristics of a former lagoon connected to the sea.…”
Section: Discussionmentioning
confidence: 99%
“…After the end of the 5th century BC, no more floods were documented at the fortifications. In general, it has been suggested [9] that the continued accumulation of sediment and low maintenance of the coastal floodplain may have contributed to the progressive silting of the river. Archaeological evidence shows that agriculture continued in the Selinunte area after 409 BC [4], and although agriculture was not as intensive as in the Greek period, it contributed to the drying up of the Cottone River.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations